Ekologi Sastra pada Kumpulan Cerpen Berbahasa Madura Ngejung Karya Mat Toyu - Abdul Wafi; Suhairi Suhairi; Moh Khalid Hasan (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to provide an understanding of the importance of caring for the environment through the study of ecological literature by analyzing literary elements in the short story collection "Ngejung" by Mat Toyu, a Madurese language literary work that describes the condition of Madura from a geographical and cultural perspective. This research uses a literary ecological analysis method with a qualitative approach. The results of the research show that "the short story collection "Ngejung" by Mat Toyu" has strong ecological elements and depicts a harmonious relationship between humans and the surrounding natural environment. These short stories also show the interactions between humans and animals, plants and creatures around where they live. The characters in the short story carry out environmentally friendly activities, such as catching fish without using chemicals or blasting or nets, and taking care of pets and plants. It is hoped that this research can provide in-depth knowledge or understanding of literary ecology in Madurese literary works and its contribution to ecological literary studies. Apart from that, it is hoped that literary ecological studies will play an important role in preserving the human environment, nature and its surroundings.